Postnatal retention in HIV care: insight from the Swiss HIV Cohort Study over a 15‐year observational period1. Issue 4 (12th August 2015) - Aebi‐Popp, K; Kouyos, R; Bertisch, B; Staehelin, C; Rudin, C; Hoesli, I; Stoeckle, M; Bernasconi, E; Cavassini, M; Grawe, C; Lecompte, TD; Rickenbach, M; et al.
Abstract : Objectives: The aim of this study was to quantify loss to follow‐up (LTFU) in HIV care after delivery and to identify risk factors for LTFU, and implications for HIV disease progression and subsequent pregnancies. Methods: We used data on pregnancies within the Swiss HIV Cohort Study from 1996 to 2011. A delayed clinical visit was defined as > 180 days and LTFU as no visit for > 365 days after delivery. Logistic regression analysis was used to identify risk factors for LTFU. Results: A total of 695 pregnancies in 580 women were included in the study, of which 115 (17%) were subsequent pregnancies. Median maternal age was 32 years (IQR 28–36 years) and 104 (15%) women reported any history of injecting drug use (IDU). Overall, 233 of 695 (34%) women had a delayed visit in the year after delivery and 84 (12%) women were lost to follow‐up. Being lost to follow‐up was significantly associated with a history of IDU [adjusted odds ratio (aOR) 2.79; 95% confidence interval (CI) 1.32–5.88; P  = 0.007] and not achieving an undetectable HIV viral load (VL) at delivery (aOR 2.42; 95% CI 1.21–4.85; P  = 0.017) after adjusting for maternal age, ethnicity and being on antiretroviral therapy (ART) at conception. Forty‐three of 84 (55%) women returned to care after LTFU. Half of them (20 of 41) with available CD4 had a CD4 count < 350 cells/μL and 15% (six of 41) a CD4 count < 200 cells/μL at their return. Conclusions: A history of IDU and detectable HIV VL at delivery were associated with LTFU. Effective strategies are warranted to retain women in care beyond pregnancy and to avoid CD4 cell count decline. ART continuation should be advised especially if a subsequent pregnancy is planned.